YAP/TAZ-TEAD is a novel transcriptional regulator of genes encoding steroidogenic enzymes in rat granulosa cells and KGN cells - Mizutani, Tetsuya; Orisaka, Makoto; Kawabe, Shinya; Morichika, Ririko; Uesaka, Miki; Yoshida, Yoshio (Molecular and cellular endocrinology, 2023)
Steroidogenesis in ovarian granulosa cells is regulated by the follicle-stimulating hormone (FSH) via transcriptional regulation of its related genes. We herein showed the involvement of the Hippo pathway in this regulation. In KGN granulosa cell, repression of YAP/TAZ activity induced the expression of CYP11A1, HSD3B2, and CYP19A1 in a TEAD-dependent manner without cAMP stimulation. A selective inhibitor of p38 MAP kinase, suppressed YAP/TAZ knockdown-indued the expression of these genes, suggesting this signal could be involved. The expression of these genes was induced by 8Br-cAMP, whereas that of CYR61 and ADATS1, typical YAP/TAZ-TEAD target genes, was suppressed, suggesting that the cellular signaling of cAMP reduced YAP/TAZ-TEAD activity. The constitutively active mutant YAP canceled the FSH- and 8Br-cAMP-mediated induction of these genes in primary rat granulosa and KGN cells, respectively. Moreover, regulation of steroidogenesis-related genes by YAP/TAZ-TEAD was independent of steroidogenic factor 1, a master gene regulator of steroidogenesis. These results suggest that YAP/TAZ-TEAD is a negative regulator of steroidogenesis and that suppression of YAP/TAZ-TEAD activity by FSH is involved in ovarian steroidogenesis. [Display omitted] •YAP/TAZ-TEAD was a negative transcriptional regulator of genes encoding steroidogenic enzymes in KGN cells.•Constitutively active YAP suppressed FSH-induced expression of steroidogenic enzymes in rat granulosa cells.•YAP/TAZ-TEAD functioned independently of SF-1.